Human CD4+ T cells specific for dominant epitopes of SARS-CoV-2 Spike and Nucleocapsid proteins with therapeutic potential - Verhagen, Johan; van der Meijden, Edith; Lang, Vanessa; Kremer, Andreas; Völkl, Simon; Mackensen, Andreas; Aigner, Michael; Kremer, Anita (Clinical and Experimental Immunology, 2021)
Since December 2019, Coronavirus disease-19 (COVID-19) has spread rapidly throughout the world, leading to a global effort to develop vaccines and treatments. Despite extensive progress, there remains a need for treatments to bolster the immune responses in infected immunocompromised individuals, such as cancer patients who recently underwent a haematopoietic stem cell transplantation. Immunological protection against COVID-19 is mediated by both short-lived neutralizing antibodies and long-lasting virus-reactive T cells. Therefore, we propose that T cell therapy may augment efficacy of current treatments. For the greatest efficacy with minimal adverse effects, it is important that any cellular therapy is designed to be as specific and directed as possible. Here, we identify T cells from COVID-19 patients with a potentially protective response to two major antigens of the SARS-CoV-2 virus, Spike and Nucleocapsid protein. By generating clones of highly virus-reactive CD4+ T cells, we were able to confirm a set of nine immunodominant epitopes and characterize T cell responses against these. Accordingly, the sensitivity of T cell clones for their specific epitope, as well as the extent and focus of their cytokine response was examined. Moreover, using an advanced T cell receptor (TCR) sequencing approach, we determined the paired TCR-αβ sequences of clones of interest. While these data on a limited population require further expansion for universal application, the results presented here form a crucial first step towards TCR-transgenic CD4+ T cell therapy of COVID-19.
CRIS-Team Scopus Importer:2021-07-09
Keywords: COVID-19; epitope; SARS-CoV-2; T cell; T cell receptor

Identification and characterization of T-cell receptors with therapeutic potential showing conserved specificity against all SARS-CoV 2 strains - Reimann, Hannah; Moosmann, Carolin; Schober, Kilian; Lang, Vanessa; Verhagen, Johan; Zeun, Julia; Mackensen, Andreas; Kremer, Anita; Völkl, Simon; Aigner, Michael (Immunobiology, 2023)
Introduction: Treatment of severe COVID-19 disease can be challenging in immunocompromized patients due to newly emerging virus variants of concern (VOC) escaping the humoral response. Thus, T cells recognizing to date unmutated epitopes are not only relevant for patients’ immune responses against VOC, but might also serve as a therapeutic option for patients with severe COVID-19 disease in the future, e.g. following allogenic stem cell transplantation. Methods: To this purpose, the activation, cytokine profile and specificity of T-cell clones against unmutated and omicron Spike (S)-protein was analyzed, HLA restriction was determined and most promising T-cell receptor (TCR) was introduced into allogeneic T cells via CRISPR/Cas9-mediated orthotopic TCR replacement. Finally, T-cell responses of engineered T cells was determined and durability of the TCR replacement measured. Perspective: SARS-CoV-2 specific engineered T cells recognizing a genomically stable region of the S-protein of all SARS-CoV 2 variants were successfully generated. Such transgenic T cells exhibit favorable effector functions and provide a treatment option of immunocompromised COVID-19 patients.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Orthotopic TCR replacement; SARS-CoV-2; T-cell engineering; T-cell therapy

Identification of human CD4(+) T cells specific for dominant epitopes of SARS-CoV-2 Spike and Nucleocapsid proteins with therapeutic potential - Verhagen, Johan; van der Meijden, Edith; Lang, Vanessa; Kremer, Andreas; Völkl, Simon; Mackensen, Andreas; Aigner, Michael; Kremer, Anita (ONCOLOGY RESEARCH AND TREATMENT, 2021)
Since December 2019, Coronavirus disease-19 (COVID-19) has spread rapidly throughout the world, leading to a global effort to develop vaccines and treatments. Despite extensive progress, there remains a need for treatments to bolster the immune responses in infected immunocompromised individuals, such as cancer patients who recently underwent a haematopoietic stem cell transplantation. Immunological protection against COVID-19 is mediated by both short-lived neutralizing antibodies and long-lasting virus-reactive T cells. Therefore, we propose that T cell therapy may augment efficacy of current treatments. For the greatest efficacy with minimal adverse effects, it is important that any cellular therapy is designed to be as specific and directed as possible. Here, we identify T cells from COVID-19 patients with a potentially protective response to two major antigens of the SARS-CoV-2 virus, Spike and Nucleocapsid protein. By generating clones of highly virus-reactive CD4+ T cells, we were able to confirm a set of nine immunodominant epitopes and characterize T cell responses against these. Accordingly, the sensitivity of T cell clones for their specific epitope, as well as the extent and focus of their cytokine response was examined. Moreover, using an advanced T cell receptor (TCR) sequencing approach, we determined the paired TCR-αβ sequences of clones of interest. While these data on a limited population require further expansion for universal application, the results presented here form a crucial first step towards TCR-transgenic CD4+ T cell therapy of COVID-19.<br
CRIS-Team WoS Importer:2022-03-25
Keywords: COVID-19; SARS-CoV-2; T cell; T cell receptor; epitope

Successful treatment of COVID-19 infection with convalescent plasma in B-cell-depleted patients may promote cellular immunity - Kremer, Andreas E.; Kremer, Anita; Willam, Carsten; Völkl, Simon; Verhagen, Johan; Achenbach, Susanne; van der Meijden, Edith; Lang, Vanessa; Aigner, Michael; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; et al. (European Journal of Immunology, 2021)
Treatment with convalescent plasma has been shown to be safe in coronavirus disease in 2019 (COVID-19) infection, although efficacy reported in immunocompetent patients varies. Nevertheless, neutralizing antibodies are a key requisite in the fight against viral infections. Patients depleted of antibody-producing B cells, such as those treated with rituximab (anti-CD20) for hematological malignancies, lack a fundamental part of their adaptive immunity. Treatment with convalescent plasma appears to be of general benefit in this particularly vulnerable cohort. We analyzed clinical course and inflammation markers of three B-cell-depleted patients suffering from COVID-19 who were treated with convalescent plasma. In addition, we measured serum antibody levels as well as peripheral blood CD38/HLA-DR-positive T-cells ex vivo and CD137-positive T-cells after in vitro stimulation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-derived peptides in these patients. We observed that therapy with convalescent plasma was effective in all three patients and analysis of CD137-positive T-cells after stimulation with SARS-CoV-2 peptides showed an increase in peptide-specific T-cells after application of convalescent plasma. In conclusion, we here demonstrate efficacy of convalescent plasma therapy in three B-cell-depleted patients and present data that suggest that while application of convalescent plasma elevates systemic antibody levels only transiently, it may also boost specific T-cell responses.
CRIS-Team Scopus Importer:2021-09-17
Keywords: B-cell deficiency; convalescent plasma; COVID-19; SARS-CoV-2; T-cell immunity

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25